Legal Protection Against Account Suspension for Digital Platform Workers: A Doctrinal and Empirical Study in Semarang, Indonesia - Nur Hidayati; Taufiq Yulianto (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
The rapid expansion of the digital platform economy has transformed employment relationships in Indonesia and created new challenges for workers’ legal protection and platform governance. This study examines the legal protection available to digital platform workers against account suspension and analyzes the role of public policy in promoting fair and accountable platform governance. The study combined doctrinal legal research with an empirical qualitative approach. Relevant Indonesian legislation and legal principles were examined through statutory and conceptual analyses, while semi-structured interviews were conducted with 20 purposively selected digital platform workers in Semarang, Indonesia. Interview data were analyzed using thematic analysis. Sixteen participants had personally experienced account suspension and reported immediate income loss, limited explanations for suspension decisions, and ineffective appeal mechanisms. The doctrinal analysis further indicates that existing Indonesian regulations provide only general legal safeguards and do not specifically regulate algorithm-based account suspension, mandatory explanations, meaningful human review, or standardized grievance procedures. The study concludes that fair platform governance requires clearer regulatory standards, transparent written explanations, accessible appeal mechanisms, and meaningful human review before permanent account suspension is imposed.